The Effects of Antitrust Enforcement Events on a Cartel Member's Stock Return and An Empirical Study of Characteristics of Firms Receiving Full Immunity. - Yuan, Heng. (2017)
Abstract: Investigation into the deterrence effect of antitrust penalties on collusive behavior has evolved significantly since the early work of Werden (1989). While it is now recognized that the ability of fines to disrupt the "no deviation" conditions necessary for successful collusion means that effective deterrence does not require fines as large as the expected collusive profit, the question of how great the disincentive for collusion is remains. In this paper, I examine a separate channel, namely, stock market reaction to price-fixing revelations. In this area, event study methodology has been quite formal and standard, thus I use this method by choosing two separate events relating to the investigation and conviction of a cartel member. On the other side, as many of the recent cartels have been discovered due to the confession by a cartel member under the Justice Department's leniency program, I also investigate the characteristics of those firms receiving leniency. The latter study is based on the model Marvao (2012) built in her study but adding several financial variables.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Economics.; Advisor: Daniel Richards.; Committee: Daniel Richards, and Marcelo Bianconi.; Keywords: Economics, and Economics, Commerce-Business.